2003
DOI: 10.1038/sj.onc.1207297
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein synthesis and expression levels in normal and neoplastic human prostate cells and their regulation by type I and II interferons

Abstract: In all, 31 differentially regulated proteins were identified by mass spectrometry analysis, several of which are involved in chaperone-assisted protein folding in the endoplasmic reticulum (ER) or in regulated protein degradation. Our results suggest that the exclusion of proteins by the ER quality control system, crosstalk between the EGF-and INF-induced signalling pathways and the regulation of INF-inducible genes are all altered in the prostate cancer cells. The combination of upregulated activity in the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 42 publications
3
42
0
1
Order By: Relevance
“…Pathways Involved in Cytokine-induced ␤-Cell Death expression of BiP/GRP78 has a protective effect on ␤-cell death (36), and the present observations on decreased BiP expression is in agreement with our previous findings on an IFN-␥-induced decrease in BiP mRNA expression (37,38). Furthermore phosphorylation of BiP results in a lower binding capacity for proteins (39,40) that, together with the above described decrease in expression of non-phosphorylated BiP, may aggravate ER stress by interfering with the clearance of unfolded or misfolded proteins (41).…”
Section: Pathways Involved In Cytokine-induced ␤-Cell Deathsupporting
confidence: 83%
“…Pathways Involved in Cytokine-induced ␤-Cell Death expression of BiP/GRP78 has a protective effect on ␤-cell death (36), and the present observations on decreased BiP expression is in agreement with our previous findings on an IFN-␥-induced decrease in BiP mRNA expression (37,38). Furthermore phosphorylation of BiP results in a lower binding capacity for proteins (39,40) that, together with the above described decrease in expression of non-phosphorylated BiP, may aggravate ER stress by interfering with the clearance of unfolded or misfolded proteins (41).…”
Section: Pathways Involved In Cytokine-induced ␤-Cell Deathsupporting
confidence: 83%
“…Enhanced expression of this hnRNP is not restricted to CML-BC, as HNRPK overexpression has also been associated with tumor progression and resistance to therapeutic drug-induced apoptosis in different types of cancer. [34][35][36][37] By assessing the mechanism whereby BCR/ABL augments HNRPK levels, we found that Hnrpk mRNA expression depends on the BCR/ABL-regulated activity of MAPK ERK1/2 . In fact, BCR/ABL-graded expression activates MAPK ERK1/2 and increases HNRPK levels in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…To assess whether the BCR/ABL-induced up-regulation of Myc expression reflects an HNRPK-dependent increase in Myc synthesis, we pulse labeled IL-3-cultured 32Dcl3 cells, and untreated and imatinib-treated 32D-BCR/ABL and S284/353A-HNRPK-expressing 32D-BCR/ABL cells with 35 [S]-methionine/cysteine and determined the levels of newly translated Myc after immunoprecipitation. Newly synthesized Myc is barely detected in 32Dcl3 cells, readily detected in BCR/ABL-expressing cells, and substantially inhibited in imatinib-treated or S284/353A-HNRPK-expressing 32D-BCR/ABL cells ( Figure 7C).…”
Section: Bcr/abl-induced Myc Expression Is Translationally Regulated mentioning
confidence: 99%
“…Interestingly, in the latter three both aberrant hnRNP K localisation and a correlation between protein expression and patient's prognosis were also observed. Until now, very little is known about the behaviour of hnRNP K in PCa; Nagano et al (2004) demonstrated that the hnRNP K was strongly overexpressed in PCa with respect to normal cell lines derived from the same patient and that the protein was differentially modulated in two cell lines by INF. More recently, Wang et al (2008) have shown that a novel transcriptional repressor complex containing Pura and hnRNP K binds the androgen receptor (AR) gene both in cell lines and in human prostate tissues.…”
mentioning
confidence: 99%